Thief of time: Academic procrastination among university youth students and its associations with self-regulation and problematic internet use - Muhd Fauzi, Nur Raihan; Mohd Mahudin, Nor Diana (Institut Penyelidikan Pembangunan Belia Malaysia (IYRES), 2021)
Previous studies on academic procrastination have underlined the importance of self-regulation for effective learning and improved academic achievement. However, the potential influence of problematic internet use on the relationship between these two variables remains largely unexplored, despite the established effects of excessive internet use on psychological well-being and overall quality of life. In an attempt to fill this gap, a total of 206 Malaysian undergraduate students completed a questionnaire containing the Academic Procrastination Scale-Short Form (APS-S: Yockey, 2016), the Self-Regulation Scale (SRS: Luszczynska et al., 2004), and the Problematic Internet Use Questionnaire Short Form (PIUQ-Sf-6: Demetrovics et al., 2016). Hierarchical multiple regression analyses indicate that both self-regulation (B = -.37, β = -.27, p < .001) and problematic internet use (B = .37, β = .33, p < .001) are significant predictors of academic procrastination. Meanwhile, results of the mediation model reveal that problematic internet use plays a mediating role in the relationship between self-regulation and academic procrastination, with indirect effect B = -.13, Boot SE = .04, CI [-.22, -.06]. These results suggest that higher levels of problematic internet use attenuate the link between high self-regulation and academic procrastination. Therefore, interventions that can enhance self-regulation as well as reduce problematic internet use have the potential to address the issue of academic procrastination in the context of universities. Implications for future research and intervention design are also discussed.